CTIM-02. TIP: PHASE I/II STUDY OF STEREOTACTIC RADIOSURGERY WITH CONCURRENT OLAPARIB FOLLOWED BY ADJUVANT DURVALUMAB AND PHYSICIAN'S CHOICE SYSTEMIC THERAPY IN SUBJECTS WITH BREAST CANCER BRAIN METASTASES. (14th November 2022) - Shen, Colette; Abdou, Yara; Tan, Xianming; Gupta, Gaorav; Lynce, Filipa; Stringer-Reasor, Erica; Anders, Carey
Abstract: BACKGROUND: Despite progress in the treatment of brain metastasis (BrM) for HER2+ breast cancer (BC), outcomes for patients with HER2-negative BC BrM remain poor. Current standard of care consists of local therapies, including surgery and radiotherapy, followed by systemic therapy. Preclinical studies show inhibitors of poly(ADP-ribose) polymerase (PARP) are effective with radiation therapy as a DNA damage response inhibitor. Triple negative BC (TNBC) has higher rates of homologous recombination deficiency compared to other BC subtypes, and together with HER2-negative, BRCA-mutated BC would be particularly sensitive to PARP inhibition. PARP inhibition also shows promising efficacy combined with immunotherapy in patients with germline BRCA-mutant and metastatic TNBC in clinical trials (MEDIOLA, TOPACIO). In addition, immunotherapy with stereotactic radiosurgery (SRS) is associated with favorable intracranial control and survival in patients with BrM. We hypothesize that this biologically-rational combination will enhance local control of SRS-treated BrM through synergy with PARP inhibition, while controlling micrometastatic disease in the brain and extracranial sites via potentiation of the immune response. METHOD: We are conducting a multi-institution, Phase I/II trial of SRS plus olaparib, followed by durvalumab (with physician's choice systemic therapy), for patients with TNBC (any BRCA status) or HER2-negative with BRCA-mutated (germline or somatic) BC BrM [NCT04711824]. The primary objectives are to evaluate safety and tolerability (Phase I) and determine intracranial disease control at 6 months (Phase II) of this treatment combination. Secondary objectives include determining clinical activity via intracranial and global progression-free survival, overall survival, and intracranial and extracranial response rate. Exploratory objectives will assess potential biomarkers of treatment response, including changes in circulating tumor cells and DNA in blood and cerebrospinal fluid, germline and tumor mutations in DNA repair pathway genes, and PD-L1 expression, as well as quality of life and patient-reported outcomes. A surgical sub-study will evaluate olaparib concentration/distribution in resected BrM.